1996
DOI: 10.1111/j.1439-0507.1996.tb00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative screening for fluconazole—amphotericin B antagonism in several Candida albicans strains by a comparative agar diffusion assay

Abstract: Antagonism between fluconazole (FCZ) and amphotericin B (AMB) was determined with an agar diffusion technique using series of agar plates containing no or 10 mgl-1 FCZ (comparative diffusion assay). Serial dilutions of AMB produced concentration-dependent inhibition zones that varied between the two agar plate series. This technique served as screening method to determine FCZ-AMB interactions in 18 Candida albicans strains. The critical concentrations of AMB were enhanced 1.33- to 7.0-fold by FCZ. The critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Antagonism among antifungal agents might occur in one of several ways. (i) Direct antifungal action at the same site results in decreased ability of other agents to exert their competitive effects on that site or at an altered target, as proposed for the azoles and amphotericin B (31,49,182,183,185,186,203). Azoles block the synthesis of ergosterol in the fungal cell membrane and may thus render amphotericin B inactive, since this agent exerts its activity by binding to ergosterol in the cell membrane.…”
Section: Mechanisms Of Interactions For the Antifungal Agentsmentioning
confidence: 99%
“…Antagonism among antifungal agents might occur in one of several ways. (i) Direct antifungal action at the same site results in decreased ability of other agents to exert their competitive effects on that site or at an altered target, as proposed for the azoles and amphotericin B (31,49,182,183,185,186,203). Azoles block the synthesis of ergosterol in the fungal cell membrane and may thus render amphotericin B inactive, since this agent exerts its activity by binding to ergosterol in the cell membrane.…”
Section: Mechanisms Of Interactions For the Antifungal Agentsmentioning
confidence: 99%
“…Depending on the conditions, up to 100% of the preexposed cells tolerated AmB at 2 g/ml for up to 24 h. However, simultaneous exposure of C. albicans to azoles and AmB had much less effect, with only a small increase in the Candida population surviving relative to controls exposed to AmB alone. Moreover, several investigators have found synergistic interactions by simulta-neous exposure of C. albicans to azoles and AmB (13,30). One group, on the other hand, described antagonisms with preexposures of Candida to the more lipophilic azoles, such as itraconazole, but not to fluconazole (31,32).…”
mentioning
confidence: 99%
“…Depending on the conditions, up to 100% of the preexposed cells tolerated AmB at 2 g/ml for up to 24 h. However, simultaneous exposure of C. albicans to azoles and AmB had much less effect, with only a small increase in the Candida population surviving relative to controls exposed to AmB alone. Moreover, several investigators have found synergistic interactions by simultaneous exposure of C. albicans to azoles and AmB (13,30). One group, on the other hand, described antagonisms with preexposures of Candida to the more lipophilic azoles, such as itraconazole, but not to fluconazole (31,32).…”
mentioning
confidence: 99%